Understanding the role of salivary proteomic markers in detecting chronic periodontitis in adults with obesity—A systematic review - Ramya, V.; Julius, Amaldas; Nisha, V. Aarthi; Bhuvaneswarri, J.; Rajendran, Karthikeyan Pandiyambakkam; Anbazhagan, Rakesh (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: This manuscript investigated the intricate relationships among obesity, chronic periodontitis (CP), and salivary proteomics. Purpose: Aiming to provide a comprehensive understanding of the molecular mechanisms underlying these interconnected health conditions. Methods: A systematic literature review was conducted in compliance with the registered PROSPERO protocol (vide number CRD42023422848). Out of 361 screened records, four articles were chosen and analyzed to examine the potential connections between obesity-related systemic inflammation, oral health decline, and changes in salivary protein profiles. Results: The major biomarkers identified were interleukin-1 beta, interleukin-6, tumor necrosis factor-alpha, matrix metalloproteinases, and alpha defensins. Conclusion: The results shared here could aid in crafting specific diagnostic and treatment approaches for those suffering from obesity and CP.